Primary Abdominal Wall Reinforcement with Synthetic Mesh Following Harvesting of Vertical Rectus Abdominis Myocutaneous Flaps in Multivisceral Pelvic Resections - Evita Zoucas; Caroline Bjarnevik; Kristina Nätterlund (Journal of Colon And Rectal Cancer, 2015)
Following multivisceral pelvic resections, the pelvis and perineum are often reconstructed using myocutaneous flaps. Abdominal wall defects after harvesting rectus abdominis flaps can be reinforced with mesh. Primary reconstruction using synthetic mesh was presently evaluated. Fifty-eight patients who underwent multivisceral pelvic resection and perineal reconstruction with a vertical rectus abdominis myocutaneous (VRAM) flap, January 2004 to February 2014, were retrospectively reviewed. The abdominal wall was reinforced in 26. Demographics, treatment procedures, surgical procedures, length of hospital and ICU stay, early and late morbidity at the recipient and donor sites were recorded. Patients with mesh reinforcement were significantly younger than those without. There were no further significant differences in patient demographics or treatment procedures between the two groups. In 31% of the patients with mesh, surgery was performed on two consecutive days, although total operating time did not differ significantly. Patients without mesh bled more. Surgery was associated with considerable morbidity, without significant differences in overall complication rate between the two groups. At the recipient site, wound infection/dehiscence was the most common early complication. The group with mesh had higher rate of total flap necrosis necessitating re-operation. At the donor site, wound infection /dehiscence, hernia, or bulge were recorded. Patients with mesh had lower rates of donor site morbidity. Perineal reconstruction with VRAM flap and primary abdominal wall reinforcement with mesh is feasible after multivisceral resection. Our study indicates that primary use of mesh can be applied in potentially contaminated surgical fields in oncologic patients without increasing morbidity and with improved long-term cosmetic results.
Keywords: multivisceral resection